The Burial from Aleti Tunu Bibi Cave, Atauro Island, East Timor: A Possible Victim of a Crocodile Attack? - Bacon, Anne-Marie; Duringer, Philippe; Ponche, Jean-Luc; Delabarde, Tania; Joannes-Boyau, Renaud; Talamo, Sahra; Tassoni, Laura; Wacker, Lukas; Ligot, Mélanie; Demeter, Fabrice; Galipaud, Jean-Christophe (Asian Perspectives: Journal of Archeology for Asia & the Pacific, 2025)
The Aleti Tunu Bibi cave, located on the small volcanic island of Atauro close to the island of Timor, is a sacred site for the region's inhabitants. The cave's archaeological potential was revealed in 2015 with the discovery of artifacts, rock art depicting marine fauna (mammals and reptiles), human remains, and a few remains of marine and terrestrial fauna. New material discovered in 2017 included sporadic remains of marine fauna, goats, and pigs, and a partial human skeleton with perimortem bone lesions. The analysis of these additional elements is presented here. Direct dating of the skeleton (14C AMS and U-series on bones and teeth) gave a burial date of ca. 4900 cal. b.p., indicating that this individual lived during the Holocene. The burial context suggests a primary burial. After thorough examination of the bone lesions, it was concluded that the individual may have been attacked by a saltwater crocodile (Crocodylus porosus), which is probably represented by the zoomorphic figures painted on the cave wall. The more recent remains of goats and pigs are associated with sacrificial rituals. Overall, the evidence points to intermittent use of the Aleti Tunu Bibi cave site as early as 18,000 years ago. Rock art and the intentional human burial allow us to describe the symbolic behavior of hunter-gatherers who heavily depended on a maritime environment.